2021
DOI: 10.3390/ijms22094899
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RTK-PI3K-mTOR Axis in Gliomas: An Update

Abstract: Gliomas are the most common and challenging malignancies of the central nervous system (CNS), due to their infiltrative nature, tendency to recurrence, and poor response to treatments. Indeed, despite the advances in neurosurgical techniques and in radiation therapy, the modest effects of therapy are still challenging. Moreover, tumor recurrence is associated with the onset of therapy resistance; it is therefore critical to identify effective and well-tolerated pharmacological approaches capable of inducing du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 183 publications
(231 reference statements)
1
64
0
Order By: Relevance
“…Then, systematic bioinformatics analysis showed that cell cycle, PI3K-AKT, TGF-beta, MTORC1, NOTCH, and MYC pathways were significantly enriched in high-TRMT6 expression patients. Consistently, many studies have demonstrated that the activation of the cell cycle, PI3K-AKT, MTORC1, NOTCH, and MYC pathways enhances the progression of glioma (Parmigiani et al, 2020;Colardo and Segatto, 2021;Hajj et al, 2021). Notably, previously published literature has shown that TGF-beta ligands and its receptors exhibited low expression in low-grade gliomas (Yamada et al, 1995).…”
Section: Discussionmentioning
confidence: 56%
“…Then, systematic bioinformatics analysis showed that cell cycle, PI3K-AKT, TGF-beta, MTORC1, NOTCH, and MYC pathways were significantly enriched in high-TRMT6 expression patients. Consistently, many studies have demonstrated that the activation of the cell cycle, PI3K-AKT, MTORC1, NOTCH, and MYC pathways enhances the progression of glioma (Parmigiani et al, 2020;Colardo and Segatto, 2021;Hajj et al, 2021). Notably, previously published literature has shown that TGF-beta ligands and its receptors exhibited low expression in low-grade gliomas (Yamada et al, 1995).…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the role of FOXO1 in metabolism in U87MG cells is complex. In line with the positive impact of FOXO1 on LDHA , FOXO factors can be associated with cancer-promoting activities and even cause resistance to Temozolomide (TMZ) [ 17 , 44 , 45 ]. Previous reports have shown that a FOXO1 homolog (FOXO3) contributed TMZ resistance in GBM through promoting beta-catenin nuclear localization [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 S3). 13 10-Hydroxy-2,2,6a,6b,9,12a-hexamethyl-9-[(((S)-1-phenylethyl)amino)methyl]-1,2,3,4, 4a,5,6,6a,6b,7,8,8a,9,10,11,12,12a,12b,13,14b-icosahydropicene-4a-carboxylic acid (12). Compound 12 was obtained through the reaction with (S)-1-phenylethanamine as a white solid (31 mg, 22%); mp 240-243 • C. 1 H NMR (600 MHz, DMSO-d 6 ) δ 7.33-7.29 (m, 4H), 7.22-7.20 (m, 1H), 5.15 (s, 1H), 3.58 (q, J = 6.6 Hz, 1H), 2.74 (dd, J = 13.5, 4.4 Hz, 1H), 2.58 (d, J = 12.0 Hz, 1H), 1.91 (d, J = 12.0 Hz, 2H), 1.80 (dd, J = 7.5, 3.1 Hz, 1H), 1.66-0.99 (m, 20H), 1.26 (d, J = 6.6 Hz, 3H), 1.11 (s, 3H), 0.88 (s, 6H), 0.85 (s, 3H), 0.68 (s, 3H), 0.63 (s, 3H) (Figure S5).…”
Section: General Methods Of the Preparation Of Compounds 10-13mentioning
confidence: 99%
“…The efficacy of anti-glioma chemotherapy is limited because of poor drug delivery and inherent chemoresistance [3] or acquired chemoresistance (e.g., to TMZ) after initial treatment [12]. Due to unfavorable pharmacokinetics of chemotherapeutic drugs, poor drug delivery across the blood-brain barrier (BBB) and blood-tumor barrier (BTB) prevents them from exerting their therapeutic action properly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation